Exploring the readiness for business proposal pitching video activity using the competition-based learning model among accounting students - Joseph, Corina (Tanjong Malim, 2021)
Exploring the readiness for business proposal pitching video activity using the competition-based learning model among accounting students by Joseph, Corina